Experimental study of the effect of teriparatide on a medication-related rat model of osteonecrosis of the jaw - LIAO Chenyu; XU Luchen; LI Yunfeng (Kouqiang hemian waike zazhi)
[Objective:] To establish a stable model of medication-related osteonecrosis of the jaw (MRONJ), and to explore the therapeutic effect of teriparatide on MRONJ. [Methods:] 10-month-old SD rats were selected and injected with zoledronic acid (80 μg/kg) via tail vein once a week for 7 weeks; the first and second molars of the right maxillary were extracted in the 8th week. Eight weeks after tooth extraction, the rat jaw osteonecrosis was observed. The animals with successful modeling of osteonecrosis of the jaw were randomly divided into the control group and the experimental group, and received subcutaneous injection of saline and teriparatide (60 μg/kg, 3 times a week), respectively. The animals were sacrificed 4 weeks later. Histology and micro-CT analysis were performed to evaluate the therapeutic effect of teriparatide on MRONJ. [Results:] In the control group, the rat jaw osteonecrosis did not heal, and the degree of necrosis was aggravated. Micro-CT images showed disordered jaw texture, rough margins, and sequestrum formation. The bone destruction area communicated with the paranasal sinus. In the experimental group, the extraction wounds were gradually reduced, and 67% of the extraction wounds in the rats were completely healed; micro-CT images showed new bone formation in the extraction wound and the signs of alveolar bone healing. Conclusion: Teriparatide has a significant therapeutic effect on MRONJ in rats.